Adverse childhood experiences, emotional distress and dissatisfaction with motherhood among first-time mothers: Mediations and child differences - Tosin Yinka Akintunde; Shaojun Chen; Stanley Oloji Isangha; Qi Di (Cambridge Prisms: Global Mental Health, 2024)
Despite the challenges associated with motherhood, studies have not consistently identified factors contributing to first-time mothers’ dissatisfaction with motherhood in resource-limited regions. To fill this research gap, this study investigates how adverse childhood experiences (ACEs) result in first-time mothers’ dissatisfaction with motherhood through emotional distress in Nigeria. Results from the partial least square structural equation model suggests that ACEs are associated with dissatisfaction with motherhood (